The Influence of E-Wallets on the Consumptive Behavior Generation Z: Systematic Review - Kuswardhani, Epifaniga Lintang; Sari, Margaretha Ananda Nurachma Pravita; Yuniawan, Ahyar; Kusumawardhani, Amie (Economic and Business Horizon, 2025)
This study investigates the impact of e-wallet usage on the consumer behavior of Generation Z, a demographic group that is rapidly embracing digital financial technologies. As digital payment systems become increasingly integrated into daily life, especially for tech-savvy young consumers, concerns have emerged regarding their influence on financial decision-making and spending habits. E-wallets offer ease, speed, and convenience, which may lead users particularly Generation Z to engage in more frequent and impulsive purchasing behavior. Through a systematic review of existing empirical studies, this research analyzes patterns and trends in the relationship between e-wallet adoption and consumptive behavior. The findings consistently demonstrate a significant positive correlation between the frequency of e-wallet usage and an increase in consumer spending. Key factors such as user-friendly interfaces, real-time transactions, digital promotions, and perceived security are identified as major drivers behind this trend. Additionally, the review highlights the dual nature of e-wallets: while they promote financial inclusion and accessibility, they also pose risks related to financial discipline. The study concludes by emphasizing the need for enhanced financial literacy, responsible digital behavior, and strategic interventions to ensure that e-wallet usage supports rather than undermines the long-term financial well-being of Generation Z.